Shipping inside the Box: Containerization and Trade - A. Kerem Cosar; Banu Demir Pakel (Center for Economic Studies and ifo Institute (CESifo), 2017)
We quantify the effect of container technology on transport costs and trade by estimating the modal choice between containerization and breakbulk shipping using micro-level trade data. The model is motivated by novel facts that relate container usage to shipment, destination and firm characteristics. We find container transport to have a higher first-mile cost and a lower distance elasticity, making it cost effective in longer distances. At the median distance across all country pairs, the box decreases variable shipping costs between 16 to 22 percent. The box explains a significant amount of the global trade increase since its inception: a quantitative exercise suggests that Turkish and U.S. maritime exports would have been about two-thirds of what they are today in the absence of containers.
Keywords: F10; F14; 330; containerization; globalization; transportation; trade